Micro-Case Videos - Ulusoy, Fadime (IGI Global, 2020)
Teachers' professional noticing of student thinking is a complex and challenging issue as being parallel with the complexity of students' ideas. Prospective teachers do not naturally notice details of student thinking in an unedited classroom video due to complexity and limitations of classroom context. This chapter identifies micro-case videos as a particular alternative to promote prospective teachers' noticing abilities by enabling them to directly attend and interpret students' thinking and strategies. In addition to the definition and characteristics of micro-case videos, this chapter articulates the production of micro-case videos used to support prospective teachers' professional noticing abilities. A micro-case video includes a collection of selected-edited events concerning a learner's thinking on content-related tasks or problem situations in a non-classroom learning environment. Incorporating micro-case videos in video-based professional development environment promotes a detailed and focused examination of student thinking.
Keywords: 5. Gender equality; 4. Education; 10. No inequality; 3. Good health